Pengaruh Tanaman Refugia Kenikir (Cosmos Caudatus) Kombinasi Jarak Tanam Untuk Menghindari Serangan Penyakit Antraknosa Pada Tanaman Cabai Besar - Siti Fatimah; Yusriadi Marsuni; Helda Orbani Rosa (www.ulm.ac.id, 2022)
Chili is one type of vegetable that is often cultivated by farmers because of its high economic value and high nutritional value. Anthracnose (Colletotrichum spp.) is the main disease that often attacks large chili plants which can cause yield loss and destroy all cultivated plants. This study aims to determine the effect of the plant refugia kenikir (Cosmos caudatus) combined with plant spacing to avoid anthracnose disease. The method used was a factorial randomized block design (RAKF) with 2 factors, Refugia kenikir (C. caudatus) (R) and Planting Distance (J), there were 6 treatments and 4 groups so that there were 24 experimental units with each unit planted 4 plants, so we got 96 plants. Which was tested by observing the percentage of disease incidence and wet weight of fruit. The results showed that refugia kenikir (C. caudatus) plant spacing combination had no significant effect on the incidence of anthracnose disease, but the spacing treatment did affect the wet weight of fruit observed on days 105 and 120 with the highest average production in treatment J3R1 (60x120 cm). ; 60 kenikir trees) of 63.5 grams and 91.25 grams.